Monitoring infected dogs after a canine brucellosis outbreak - Reynes, Eduardo (2012)
Many episodes of canine brucellosis in dog kennels have been reported but recently an outbreak that involved pets and their owners has been described. The purpose of this study was to confirm thatthe outbreak had a common source and evaluate the evolution of 4 dogs involved in this outbreak after the measures implemented that included a survey of 41 animals from the same area. The variable number of tandem repeat (VNTR) analysis indicated that the B. canis isolated from the human clustered together with the isolates collected from the canine pups. Two dogs continued with bacteremia after the first antibiotic therapy and from one of them B. canis was also isolated from urine showing the importance of the later in the infection dissemination. In an effort to protect the public, stray dogs should be controlled and educational programs about the risk of this zoonotic disease should be implemented.